Water management reform and the choice of contractual form in China - Huang, Qiuqiong; Rozelle, Scott; Msangi, Siwa; Wang, Jinxia; Huang, Jikun (Cambridge University Press, 2008)
This paper explains the puzzling fact that in organizing the management of surface water, village leaders have provided incentives to canal managers in some areas, but not in all. Our study indicates that the optimal contractual choice depends on the relative abilities of the leader and the manager, the design of the cultivated land, the characteristics of the canal system and the opportunity costs of the leader and the pool of managerial candidates. The unifying mechanism is the relative change in the ability of the leader and manager to perform the unmarketable activities that are needed to provide irrigation services.